Krajowy Ośrodek Wsparcia Rolnictwa jako sukcesor Agencji Nieruchomości Rolnych w zakresie roszczeń pracowniczych - Litwiniuk, Przemysław (Wydawnictwo Naukowe UAM, 2017)
As of 31 August 2017, the Polish Agricultural Market Agency and the Agricultural Property Agency have been abolished and on 1 September 2017 the National Support Centre for Agriculture was established to replace both. By operation of law, the Centre has taken over all the rights and obligations of the Agricultural Property Agency. The purpose of this article is to answer the question whether the transfer of all employees of the former Agricultural Property Agency to the National Support Centre for Agriculture, following the transfer of the property and tasks of the Agricultural Property Agency was carried out in line with the provisions of Article 231 of the Labour Code, in conjunction with the directly applicable provisions of the European Council Directive 2001/23/EC of 12 March 2001 on the approximation of the laws of Member States relating to the safeguarding of employees' rights in the event of transfers of undertakings, businesses or parts of undertakings or businesses. The author states that the Agricultural Property Agency was an economic entity within the meaning of the Directive and not a public administration body. The above Directive qualifies its employees for protection resulting directly from the provisions of secondary European Union law.

A decorrere dal 31 agosto 2017 sono state abrogate l’Agenzia per il mercato agricolo e l’Agenzia per i fondi agricoli, il 1° settembre 2017, al posto loro, è stato istituito il Centro nazionale di sostegno per l’agricoltura. Ai sensi della legge, il Centro ha acquisito i diritti e gli obblighi dell’Agenzia per i fondi agricoli abrogata. I rapporti di lavoro dei dipendenti dell’Agenzia in oggetto sono stati sciolti, senza avergli offerto un impiego presso il nuovo Centro. L’articolo si propone di rispondere alla domanda se, a seguito dell’abrogazione dell’Agenzia i fondi agricoli e della successiva acquisizione del suo patrimonio e dei compiti da parte del nuovo Centro, sia avvenuto il trasferimento di tutti i dipendenti dell’Agenzia precedente, viste le disposizioni, direttamente applicabili, della direttiva 2001/23/CE del Consiglio concernente il ravvicinamento delle legislazioni degli Stati membri relative al mantenimento dei diritti dei lavoratori in caso di trasferimenti di imprese, di stabilimenti o di parti di imprese o di stabilimenti. L’autore formula la tesi secondo la quale l’Agenzia per i fondi agricoli era un ente economico ai sensi della direttiva evocata, ma non un ente amministrativo pubblico, quindi i diritti dei dipendenti andavano tutelati direttamente ai sensi della legislazione derivata dell’UE.
The National Centre for Agricultural Support as a successor to the Agricultural Property Agency in the field of employee claims
Il centro nazionale di sostegno per l’agricoltura come successore dell’Agenzia per i fondi agricoli nel campo dei diritti lavorativi